Characterization of Wireless Data Transmission over Wi-Fi in a Biomechanical Information Processing System (2019)
This paper presents a characterization of the wireless transmission of biomechanical signals in an embedded system, where a TCP protocol is used in an IEEE 802.11 communications network (Wi-Fi). The embedded system under study, called Imocap, allows the collection, analysis and transmission of biomechanical signals in real-time for various applications, among which the analysis of the movement of the lower and upper extremities and the operation of various control systems stand out. To accomplish this, Imocap is equipped with a Wi-Fi transceiver module (ESP8266) and various input and output peripherals. The wireless communication performance of Imocap, exposed in this paper, was analyzed through different tests in miscellaneous conditions like indoors, outdoors and in the presence of interference, noise and other wireless networks. The different test protocols conducted result in the Imocap system: 1) has a maximum effective range of 45.6 m when in Access Point mode; 2) has a maximum effective range of 44.3 m when in Station mode. In indoors and under the same conditions, the Imocap system: 3) has a maximum effective range of 81.25 m2, either Access Point or Station mode. The results showed that the transmission of biomechanical information through Wi-Fi using the TCP protocol is efficient and robust, both indoors and outdoors, even in environments of radio frequency interference. The use of this protocol is emphasized since its use allows the transmission of packages to be carried out in a controlled manner, allowing the error handling and recovery. In this way, it is possible to carry out efficient and robust wireless communication through embedded and portable devices, focusing mainly on areas such as medicine, telemedicine and telerehabilitation.